Residential Land Prices Changes and Tourism Development in Watukarung Village Pacitan Regency Within Local Communities Perspective - Ekky Elfira Kusumawardhani; Sri Rum Giyarsih (Department of Geography Education, University of Jember, 2023)
Tourism objects in Pacitan Regency are increasingly diverse and attract tourists from within and outside the region to visit. The price of residential land is one aspect that has also changed along with these developments. The phenomenon of changes in land prices also occurred in Watukarung Village. This study aims to analyze changes in the price of residential land and its relation to tourism developments that occurred in Watukarung Village based on the perceptions of the local community. The method used is qualitative with data collection techniques in the form of in-depth interviews. The data from the interviews were processed using data reduction techniques so that a unit of information was obtained which could then be analyzed descriptively qualitatively. The accuracy of the data obtained was tested using a data source triangulation technique that compared the results of one informant with another. The result shows that the development of tourism has attracted foreign tourists to come and buy residential land in Watukarung Village. The price of residential land by the beach was originally around IDR 300,000/m2 increase to IDR 1,000,000 to IDR 1,500,000/m2. Based on the perception of the local community, the significant increase in the price of residential land is closely related to the development of tourism that has taken place in Watukarung Village. However, there are also people who have the perception that rising residential land prices and tourism development have no direct relationship. Keywords : Land Prices; Settlements; Tourism Development Copyright (c) 2023 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License